(untitled) (Bangladesh Journal of Medical Biochemistry, 2025)
Type 2 diabetic patients with poor glycemic control are more prone to dyslipidemia which has been suggested as a modifiable risk factor for the atherosclerotic macrovascular complications. Glycated hemoglobin (HbA1c) is considered as good indicator of long-term glycemic control as well as predictor of lipid profile. Early detection and treatment of lipid abnormalities can reduce the risk for cardiovascular disease in patients with type 2 diabetes mellitus (T2DM). Such type of studies in our country are limited. So we planned to evaluate the association of HbA1c with lipid profile among patients with type 2 diabetes at Chittagong Medical College Hospital, Bangladesh. This cross-sectional analytical study was carried out in the department of Biochemistry, Chittagong Medical College, Bangladesh from July 2020 to June 2021. A total 120 patients with T2DM aged 40-75 years were selected from outpatient department of Endocrinology, Chittagong Medical College Hospital by non-probability purposive sampling. Fasting blood glucose (FBG), HbA1c, fasting total cholesterol (TC), triglyceride (TG), low density lipoprotein (LDL-C), high density lipoprotein (HDL-C) were evaluated and lipid profile were compared between good glycaemic control (HbA1c<7%) and poor glycaemic control (HbA1c≥7%) group. There were 56 males and 64 females among 120 T2DM patients in this study. The mean age±SEM (60.48±1.06) of male patients was significantly higher than that of female patients (53.83±1.26). There was a highly significant positive correlation between HbA1c and FBG (r=0.854, p<0.001). HbA1c and FBG had significant positive correlation with TC, TG, LDL-C, and significant negative correlation with HDL-C; the strength of significance for all lipid parameters being greater with HbA1c than FBG. Increased TC, TG, LDL-C, and decreased HDL-C were significantly associated with poor glycemic cases. HbA1c was a predictor of TC, TG, HDL-C and LDL-C in T2DM patients on linear regression analysis. The present study revealed that HbA1c significantly correlated with TC, TG, LDL-C and HDL-C. It is also found that there is a significant difference in lipid profiles between good and poor glycemic control cases. Thus, using HbA1c to monitor glycemic control may also have the added benefit of helping to identify type 2 diabetes people who are more vulnerable to cardiovascular complications. Bangladesh J Med Biochem 2021; 14(2): 49-58